Mechatronics and computational mechanics II : selected, peer reviewed papers from the 2013 2nd International Conference on Mechatronics and Computational Mechanics (ICMCM 2013), December 30-31, 2013, Frankfurt, Germany - Mourad, Abdel Hamid Ismail; Tar, József Kázmér (Applied mechanics and materials ;, 2014)
Collection of selected, peer reviewed papers from the 2013 the 2nd International Conference on Mechatronics and Computational Mechanics (ICMCM 2013), December 30-31, 2013, Frankfurt, Germany. The 62 papers are grouped as follows: Chapter 1: Materials Research, Chapter 2: Applied Mechanics, Chapter 3: Design, Modelling and Simulation, Chapter 4: Robotic, Sensors and Control Systems, Chapter 5: Information and Computer Technologies Keyword: Materials Research, Applied Mechanics, Design, Modelling and Simulation, Robotic, Sensors and Control Systems, Information and Computer Technologies In this collection, engineers and other scientists from Asia, Iran, Algeria, and Europe present 62 papers from the Second International Conference on Mechatronics and Computational Mechanics (ICMCM 2013), held in December 2013 in Frankfurt, Germany. Topics include applied mechanics; design, modeling, and simulation; robotic, sensors, and control systems; information and computer technologies; and materials research. -- Classical mechanics-- Computational physics-- Materials science.